2011
DOI: 10.1002/bem.20697
|View full text |Cite
|
Sign up to set email alerts
|

No effects of short‐term exposure to mobile phone electromagnetic fields on human cognitive performance: A meta‐analysis

Abstract: During recent years, a large number of studies on the effects of electromagnetic fields emitted by cellular mobile phones on human cognitive performance have been carried out. However, the results have been ambiguous. We carried out the current meta-analysis in order to investigate the impact of electromagnetic fields emitted by mobile phones on human cognition. Seventeen studies were included in the meta-analysis as they fulfill several requirements such as single- or double-blind experimental study design, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…() and Barth et al . () reported no effects of exposure. These meta‐analyses have several limitations in the context of assessing the effects of EMF on WM.…”
Section: Introductionmentioning
confidence: 97%
“…() and Barth et al . () reported no effects of exposure. These meta‐analyses have several limitations in the context of assessing the effects of EMF on WM.…”
Section: Introductionmentioning
confidence: 97%
“…The current review reopens the question of whether MP EMF exposure affects brain function. Previous reviews of studies prior to 2011 have suggested that there is no effect of short‐term exposure to MP EMFs on human cognitive performance [Valentini et al, ; Barth et al, ]. Several studies in the current review point to an increase in cortical excitability and/or efficiency during exposure that may persist for several minutes post‐exposure.…”
Section: Discussionmentioning
confidence: 69%
“…reported that the cognitive abilities neither impaired nor facilitated electromagnetic fields emitted by GSM and Universal Mobile. [19] Neither heating nor overproduction of reactive oxygen species explain the cardiac effect of mobile in this study because the subjects were exposed to short duration of electromagnetic energy (40 sec). Yuasa et al .…”
Section: Discussionmentioning
confidence: 90%